2021
DOI: 10.1021/acs.jpclett.0c03461
|View full text |Cite
|
Sign up to set email alerts
|

Probing Excitons in Ultrathin PbS Nanoplatelets with Enhanced Near-Infrared Emission

Abstract: Strongly quantum-confined 2D colloidal PbS nanoplatelets (NPLs) are highly interesting materials for near-infrared optoelectronic applications. Here, we use ultrafast transient optical absorption spectroscopy to study the characteristics and dynamics of photoexcited excitons in ultrathin PbS NPLs with a cubic (rock-salt) structure. The NPLs are synthesized at near room temperature from lead oleate and thiourea precursors and show an optical absorption onset at 680 nm (1.8 eV) as well as photoluminescence at 72… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…Ultrafast broadband transient optical absorption spectroscopic measurements were performed on a setup similar to that described in the literature. , Briefly, a 100 fs laser pulse train from a Ti/sapphire amplifier system (Spectra-Physics, Spitfire ACE) centered at 800 nm is used and split (90:10) to generate a pump and probe beam. A broadband supercontinuum is generated by non-linear processes inside a CaF 2 or sapphire crystal (320–1600 nm) with 10% of the fundamental.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrafast broadband transient optical absorption spectroscopic measurements were performed on a setup similar to that described in the literature. , Briefly, a 100 fs laser pulse train from a Ti/sapphire amplifier system (Spectra-Physics, Spitfire ACE) centered at 800 nm is used and split (90:10) to generate a pump and probe beam. A broadband supercontinuum is generated by non-linear processes inside a CaF 2 or sapphire crystal (320–1600 nm) with 10% of the fundamental.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of PbSe NPLs is based on a method by Manteiga Vázquez et al 29 The precursor formation steps and the reaction were run under inert gas conditions either inside a glovebox or on a Schlenk apparatus. The syntheses at 0 °C were conducted using an ice bath.…”
Section: Methodsmentioning
confidence: 99%
“…In such a column structure, excitons can be transported between the close-packed nanoplatelets by FRET, which would be quenched when they encountered nonemissive nanoplatelets. For a deep understanding of the dynamics of photoexcited charge carriers in colloidal nanoplatelets, a combination of TRPL, transient absorption (TA), and terahertz (THz) spectroscopic techniques would be required. Siebbeles et al studied the decay dynamics of excitons in CdSe/CdS platelets and found that the band-to-band relaxation and the trap-induced decay occurred on a time scale of hundreds of picoseconds . By means of optical pump–terahertz probe spectroscopy, they extracted the frequency-dependent alternating current mobility of colloidal Cd-based nanoplatelets, which displayed a significant decrease compared to the value of its bulk counterpart.…”
Section: Spectroscopic Characterizationsmentioning
confidence: 99%